Off-label underdosed apixaban use in Asian patients with non-valvular atrial fibrillation. Issue 5 (20th January 2021) - Lee, So-Ryoung; Choi, Eue-Keun; Park, Sang-Hyun; Jung, Jin-Hyung; Han, Kyung-Do; Oh, Seil; Lip, Gregory Y H
Abstract: Aims: To compare the effectiveness and safety of off-label underdosed apixaban with on-label standard dose apixaban in Asian patients with atrial fibrillation (AF). Methods and results: Using the Korean nationwide claims database, we identified patients who were prescribed apixaban and did not fulfil the dose reduction criteria for apixaban between January 2015 and December 2017. A multivariable Cox hazard regression model was performed, and hazard ratios (HRs) for ischaemic stroke, major bleeding (MB), all-cause death, and composite outcome were analysed. Compared to patients prescribed on-label standard dose apixaban ( n  = 4194), patients prescribed off-label underdosed apixaban ( n  = 2890) showed a higher risk of ischaemic stroke [adjusted HR (aHR) 1.38, 95% confidence interval (CI) 1.06–1.81], all-cause death (aHR 1.19, 95% CI 1.01–1.39), and the composite outcome (aHR 1.17, 95% CI 1.03–1.34), but with no significant differences in MB between the two groups. Among the patients who did not meet any dose reduction criteria, off-label underdosed apixaban use was associated with a significantly higher risk of ischaemic stroke than on-label standard dose apixaban use (aHR 1.85, 95% CI 1.25–2.73). Among the patients who met a single dose reduction criterion, off-label underdosed apixaban use was associated with a higher risk of all-cause death than on-label standard dose apixaban (aHR 1.32, 95% CI 1.07–1.64). Conclusion: The off-label underdosed apixaban group showed higher risks of ischaemic stroke, all-cause death, and composite clinical outcomes than the on-label standard dose apixaban group, but both showed comparable risks of MB. Label adherence to apixaban dosing should be emphasized to achieve the best clinical outcomes for Asian patients with AF.